Libraries and Public Education in Rural Kareliya (Late 19th — Early 20th) - Olga P. Ilyukha; Ольга Павловна Илюха (Bibliotekovedenie [Library and Information Science (Russia)], 2009)
Peculiarities of library services in Olonetsky Karelia, the Northwest suburb of Russian empire, are described in the article as well as various forms of library services, including activities of the first mobile libraries. The role of libraries in development of national education and increase of school attractiveness for peasants is shown. Horizons of reading of a countryman is outlined. Рассматриваются особенности организации библиотечного дела на северо-западной окраине Российской империи, в Олонецкой Карелии, раскрываются различные формы библиотечной работы, включая деятельность первых передвижных библиотек. Показана роль библиотек в развитии народного образования и повышении привлекательности школы для крестьян. Характеризуется круг чтения сельского жителя.